The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10566-022-09673-1
|View full text |Cite
|
Sign up to set email alerts
|

Supporting School Mental Health Providers: Evidence from a Short-Term Telementoring Model

Abstract: Background To support student mental health, school staff must have knowledge of evidence-based practices and the capacity to implement them. One approach used to address this challenge is a group-based telementoring model called Extension for Community Healthcare Outcomes (ECHO). In other applications (e.g., healthcare settings), ECHO has been shown to increase healthcare professionals’ self-efficacy and knowledge of evidence-based practices leading to improved patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Compared to Modules only participants, ECHO + Modules participants demonstrated significantly greater improvements in their collaborative processes ( d = 1.22), and effect size estimates revealed moderate positive impacts of ECHO on participants’ knowledge of evidence-based and culturally competent practices. Like previous studies, we found that ECHO participation was associated with increased engagement with supplementary learning modules (Lyons et al, 2022). However, Modules only participants who returned post-training surveys demonstrated similar levels of module engagement as those in the ECHO condition.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Compared to Modules only participants, ECHO + Modules participants demonstrated significantly greater improvements in their collaborative processes ( d = 1.22), and effect size estimates revealed moderate positive impacts of ECHO on participants’ knowledge of evidence-based and culturally competent practices. Like previous studies, we found that ECHO participation was associated with increased engagement with supplementary learning modules (Lyons et al, 2022). However, Modules only participants who returned post-training surveys demonstrated similar levels of module engagement as those in the ECHO condition.…”
Section: Discussionsupporting
confidence: 87%
“…When professional development is delivered in short bursts, it rarely contributes to long-term, sustainable change (Darling-Hammond et al, 2017). The ECHO model offers an accessible, reliable, low-cost, and scalable platform for prolonged engagement and interdisciplinary collaboration (Lyons et al, 2022). These factors are critical to consider when selecting professional learning/training for school counselors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations